Kritik “INSISTS” Terhadap Gagasan Pluralisme Agama - Fata, Ahmad Khoirul; Fauzan, Fauzan (KALAM, 2017)
The theology of religious pluralism presented as a solution to resolve the conflict in a multi-religious society. But this idea is very debatable in the Indonesian Muslim community. One of the groups refuses aloud is a group of young intellectuals who are members of the Institute for the Study of Islamic Thought and Civilization (INSISTS). This paper describes the arguments used in the INSISTS activists criticized the idea of religious pluralism. Instead of a solution, INSISTS activists assess religious pluralism is a new problem in a multi-religious society. The problem lies in some respects, namely socio-historical context is different between Muslim societies and the West where the first time the idea came, also contains the idea of pluralism rated parallelism religious truth and relativism of truth. The negative side is what makes religious pluralism is not the solution in building harmony in a plural society, but it gave birth to syncretism and relativism of religious truth. INSISTS activists viewed the idea of religious pluralism as a foreign idea that is contrary to Islamic faith and the teachings. Due to the application of the religious pluralism theology in Islam can damage the principal Islamic faith and teachings.